East Central Europe and Communism Politics, Culture, and Society, 1943-1991 - Ramet, Sabrina P. (Routledge Open History, 2023)
The communists of East Central Europe came to power promising to bring about genuine equality, paying special attention to achieving gender equality, to build up industry and create prosperous societies, and to use music, art, and literature to promote socialist ideals. Instead, they never succeeded in filling more than a third of their legislatures with women and were unable to make significant headway against entrenched patriarchal views; they considered it necessary (with the sole exception of Albania) to rely heavily on credits to build up their economies, eventually driving them into bankruptcy; and the effort to instrumentalize the arts ran aground in most of the region already by 1956, and, in Yugoslavia, by 1949. Communism was all about planning, control, and politicization. Except for Yugoslavia after 1949, the communists sought to plan and control not only politics and the economy, but also the media and information, religious organizations, culture, and the promotion of women, which they understood in the first place as involving putting women to work. Inspired by the groundbreaking work of Robert K. Merton on functionalist theory, this book shows how communist policies were repeatedly undermined by unintended consequences and outright dysfunctions.